De la ciudad civil a la ciudad social: concepciones de gobierno en Buenos Aires (1880-1955) - Matías Landau (Nuevo mundo - Mundos Nuevos, 2012)
Between late nineteenth and mid twentieth century took place a transformation, when the City of Buenos Aires was conceived as an object of government. When the federalization occurred in 1880, political and academic elites followed the mainstream of nineteenth-century municipalism (called domestic approach). According to this, city government was intended to deal merely with ‘the civic life of taxpayer-neighbors’. In the '20s and '30s, with urban growth and a more complex society, we witnessed the development of a ‘social approach’ to city government. The social city, that replaced the civic city, was in turn replaced by a social government of the nation, during the rise of Peronism.